Research on Automatic Configuration of Helicopter Transmission Systems Based on Graph Theory - Li, Xiaokang; Yang, Xiaohui; Han, Bing; Chen, Keming (IEEE International Conference on Industrial Technology (Online), 2025)
The development of helicopter transmission systems consumes a significant amount of funding during the early stages of helicopter design, with conceptual design playing a critical role in the overall design of the transmission system. This paper leverages the fundamental principles of graph theory to transform helicopter transmission relationship units and connection relationships into vertex models recognizable by computers. A method for designing helicopter main gearbox concepts is proposed, enabling the exhaustive generation of numerous transmission schemes. Additionally, transmission models are automatically generated through a com-bination of hierarchical layouts and parallel transmission path branching methods.